3D LTCC structure for a large-volume cavity-type chemical microreactor. Issue 3 (3rd August 2015) - Belavič, Darko; Hrovat, Marko; Makarovič, Kostja; Dolanč, Gregor; Pohar, Andrej; Hočevar, Stanko; Malič, Barbara
Abstract : Purpose: – The purpose of this paper is to present the research activity and results to research and development society on the field of ceramic microsystems. Design/methodology/approach: – The chemical reactor was developed as a non-conventional application of low temperature co-fired ceramic (LTCC) and thick-film technologies. In the ceramic reactor with a large-volume, buried cavity, filled with a catalyst, the reaction between water and methanol produces hydrogen and carbon dioxide (together with traces of carbon monoxide). The LTCC ceramic three-dimensional (3D) structure consists of a reaction chamber, two inlet channels, an inlet mixing channel, an inlet distributor, an outlet collector and an outlet channel. The inlet and outlet fluidic barriers for the catalyst of the reaction chamber are made with two "grid lines". Findings: – A 3D ceramic structure made by LTCC technology was successfully designed and developed for chemical reactor – methanol decomposition. Research limitations/implications: – Research activity includes the design and the capability of materials and technology (LTCC) to fabricate chemical reactor with large cavity. But further dimensions-scale-up is limited. Practical implications: – The technology for the fabrication of LTCC-based chemical reactor was developed and implemented in system for methanol decomposition. Originality/value: – The approach (large-volume cavity in ceramic structure), which has been developed, can be used for other type of reactors also.